Resveratrol v kozmetiki in dermatologiji - Bolko Seljak, Katarina (Farmacevtski vestnik, 2023)
We have been facing an increase in the use of resveratrol as an ingredient in skincare and dermatology, utilising its antioxidative activity and ability to penetrate the skin barrier. This has enabled the discovery of the previously unknown benefits of its dermal use, caused by the antioxidative, anti-inflammatory, regenerative, anti-cancer and antimicrobial activity of this molecule. In the future, more resveratrol-based skincare is thus expected on the market, intended for ageing skin, unclear skin, skin regeneration and skin with pigmentation disorders. Despite the progress, there has been a lack of in vivo studies in the scientific field that would help in the determination of the optimal concentration of resveratrol in dermocosmetics and its formulation with the optimal ratio between effectiveness and safety.
Keywords: Dermatologija; Kozmetika; Koža; resveratrol; Staranje